Dampak Burnout Terhadap Well - Being Di Mediasi Resilience (Studi Pada Dosen Swasta Di Kota Medan) - Tarmiati, Erni; Sunaryo; Ardiani, Winda (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This study aims to determine the impact of Burnout on Well-Being with Resilience as a mediating variable on private lecturers in Medan City. The sample used totals 176 respondents. This study uses the SEM-PLS model as an analytical technique that can justify the effect of independent variables on the dependent variable either directly or indirectly through mediating variables. The results of this study indicate that the Burnout variable has a negative and significant effect on Well-Being directly. Burnout has a negative and significant effect on Resilience. Resilience has a positive and insignificant effect on Well- Being. Resilience variable is not able to mediate the relationship between Burnout and Well-Being